Osteological description of the taruca (Hipocamelus antisensis) (d'Orbigny, 1834): II. Axial skeleton - Zapata Coacalla, Celso (2021)
Hippocamelus antisensis (d'Orbigny 1834), commonly called taruca, is a deer that lives in Peru, Bolivia and Chile between 3500 to 5000 m, and is considered a vulnerable species. The axial skeleton of the taruca is described based on four specimens (two males and two females), according to authorization RDG N° 158-2015-SERFOR-DGGSPFFS. The bone pieces were obtained according to the anatomical technique, the description is in accordance with the Veterinary Anatomical List and the measurements as described by Von den Driesch. In the skull, the occipital does not have a very prominent occipital protrusion, the frontal bone is characterized by its horn process and by presenting up to three supraorbital foramina, the lacrimal has a deep fossa and a fissure covered by cartilage, the incisor bone and maxilla are elongated, in the maxilla there is the presence of a dental socket for the canine, the symphysis of the mandible remains until adulthood, the vomer projects caudally relating to the palatine bone, it has 7 cervical vertebrae, 13 thoracic, 7 lumbar, 5 sacral and 7 coccygeal and the sternum with 7 sternebrae, presents a pronounced xiphoid process. It is concluded that the head is elongated due to the characteristics of the maxillary and incisor bones, the presence of foramina and the characteristics of the antlers in the frontal bone can be used for its identification, the existence of the deep lacrimal fossa and a covered fissure. by cartilage, the choanas are divided by the vomer.